2004
DOI: 10.1111/j.1751-0813.2004.tb14650.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of avian paramyxoviruses and influenza viruses amongst wild bird populations in Victoria

Abstract: Twenty-five viruses were isolated, none of which resembled progenitor or virulent genotypes. This study provides valuable epidemiological information against which to compare future isolates from outbreaks of disease to determine their origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…Of all the LPAI subtypes identified in wild birds from other parts of the world, most have also been found in Australia (Downie and Laver 1973;Downie et al 1977;Mackenzie et al 1984Mackenzie et al , 1985Nestorowicz et al 1987;Peroulis and O'Riley 2004;Hurt et al 2006;Haynes et al 2009), including subtypes H5 and H7 (which have potential for HPAI phenotype; see Box 1). Studies on AIV gene segments isolated from wild birds in Australia indicate these viruses maintain phylogenetic relationships with those from Eurasia and, to a lesser extent, North America (Donis et al 1989;Banks et al 2000;Kishida et al 2008).…”
Section: Which Aivs Are Found In Australian Wild Birds?mentioning
confidence: 99%
“…Of all the LPAI subtypes identified in wild birds from other parts of the world, most have also been found in Australia (Downie and Laver 1973;Downie et al 1977;Mackenzie et al 1984Mackenzie et al , 1985Nestorowicz et al 1987;Peroulis and O'Riley 2004;Hurt et al 2006;Haynes et al 2009), including subtypes H5 and H7 (which have potential for HPAI phenotype; see Box 1). Studies on AIV gene segments isolated from wild birds in Australia indicate these viruses maintain phylogenetic relationships with those from Eurasia and, to a lesser extent, North America (Donis et al 1989;Banks et al 2000;Kishida et al 2008).…”
Section: Which Aivs Are Found In Australian Wild Birds?mentioning
confidence: 99%
“…A wide range of low pathogenicity strains of avian influenza (LPAI) have been reported in wild bird species within Australia, including all H types except H10, H14, and H16 (Downie and Laver 1973, Downie et al 1977, Mackenzie et al 1984, Mackenzie et al 1985, Nestorowicz et al 1987, Rohm et al 1996, Peroulis and O'Riley 2004, Tracey et al 2004, Turner 2004, Hurt et al 2006). Tracey et al (2004) and Sims and Turner (2008) provide an overview of these reports.…”
Section: Avian Influenza In Australian Wild Birdsmentioning
confidence: 99%
“…In other studies Charadriiformes (shorebirds, plovers and lapwings) (Kawaoka et al 1988) and spoonbills (Astorga et al 1994) have also been found to have a high prevalence of the virus, with isolation rates of up to 20% and 32% respectively. In Australia, prevalence of the virus is found to be much lower (Mackenzie et al 1984(Mackenzie et al , 1985Peroulis and O'Riley 2004). Isolation rates and subtypes vary considerably over time, region and between species (Kawaoka et al 1988;Sharp et al 1993).…”
Section: Occurrence Of Avian Influenza In Wild Birdsmentioning
confidence: 99%
“…Most subtypes (H1, H3, H4, H5, H6, H7 1 , H11, H12) have been detected in Australian wild birds (Downie and Laver 1973;Downie et al 1977;Mackenzie et al 1984Mackenzie et al , 1985Nestorowicz et al 1987;Peroulis and O'Riley 2004). In Australia, no quantitative links have been made to wild birds during the five previous HPAI outbreaks in poultry.…”
Section: Occurrence Of Avian Influenza In Wild Birdsmentioning
confidence: 99%
See 1 more Smart Citation